Aboveground Biomass and Nutrient Pools in Two Evergreen Oak Stands of the Middle Moroccan Atlas Area - Boulmane, Mohamed; Santa-Regina, Ignacio; Khia, Abderrahim; Abbassi, Hassan; Halim, Mohamed (Arid Land Research and Management, 2013)
The aboveground tree biomass and nutrient pools, litterfall, and weight loss of litter due to decomposition have been measured in two permanent plots of evergreen oak forest (Quercus ilex L.) of the Middle Moroccan Atlas area (Tafachna and Reggada). The aboveground biomass was estimated by cutting and weighing twenty trees Y (biomass)¼aX (X¼(D2H)b, D and H are respectively the diameter at 1.30m and tree height. The aboveground biomass of the two studied stands was: 96.0 and 86.4 t ha1, respectively, for Tafachna and Reggada of which the woody part accounts for approximately 96%. The average productions of litter are, respectively, 3030 and 3560 kg ha1 yr1 for Tafachna and Reggada. The leaves account for approximately 70% of the total litterfall, restored to the soil 38.3 kg ha1 yr1 for Tafachana and 44.6 kg ha1 an1 for Reggada (approximately 74% of the total nutrient amount of the litterfall). The decomposition pattern of the leaves litter from each site according to diameter classes. In order to establish biomass regression equations the best fit was obtained by applying the allometric method: follows a negative exponential equation of form RF¼A þB exp (kt). The nitrogen was the bioelement that contributed the greatest amount to the bio- geochemical cycling between vegetation and soil. At the level of internal exchange to the trees, translocation, and transfer, the nitrogen was followed by phosphorus and potassium.
Keywords: aboveground biomass; allometric method; forest ecosystem; litter decomposition; nutrient storage; Quercus ilex

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex - Cherbuy, Bénédicte; Joffre, Richard; Gillon, Dominique; Rambal, Serge (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.910.1093/treephys/21.1.9
Keywords: defoliation; Growth; nutrient storage; resource remobilization

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex - Cherbuy, Bénédicte; Joffre, Richard; Gillon, Dominique; Rambal, Serge (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.9
Keywords: defoliation; Growth; nutrient storage; resource remobilization